2021
DOI: 10.1002/rth2.12556
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality‐of‐life questionnaires for deep vein thrombosis and pulmonary embolism: A systematic review on questionnaire development and methodology

Abstract: To improve the quality and accuracy of the patient‐reported outcome measures that assess health‐related quality of life (HRQoL), guidelines have been developed to standardize the development and validation process. Considering the increasing importance of HRQoL questionnaires in research, we set out to review the literature and evaluate whether existing questionnaires developed for deep vein thrombosis (DVT) and pulmonary embolism (PE) fulfill state‐of‐the‐art requirements. The literature search was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
(122 reference statements)
0
9
0
Order By: Relevance
“…[ 15 ] structured dimensions through clinical concepts and patient interviews for the current version of the questionnaire. However, the suggested structure should be bolstered through exploratory factor analysis before the confirmatory process [ 8 , 12 ]. Our EFA suggested a 3-factor structure closely resembling the study of the French population [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 15 ] structured dimensions through clinical concepts and patient interviews for the current version of the questionnaire. However, the suggested structure should be bolstered through exploratory factor analysis before the confirmatory process [ 8 , 12 ]. Our EFA suggested a 3-factor structure closely resembling the study of the French population [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chronic complications of acute PE are also taxing on one’s psychological and social status. The long-term risk of purchasing psychotropic drugs is substantially increased in adolescents with a history of PE, with more than a quarter of the previously employed patients not returning to work even one year after the initial PE episode [ [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%
“…The first and only disease- specific questionnaire is the Pulmonary Embolism-Quality of Life (PEmb-QoL) questionnaire [ 26 , 27 ]. A systematic review assessing the methodology and development of instruments about HRQoL questionnaires for patients with venous thromboembolism concluded that none of the available instruments fulfill the guideline recommendations and, due to other methodological limitations, their use in everyday practice has limitations [ 28 ].…”
Section: Mental Health Aspects Of Pulmonary Embolismmentioning
confidence: 99%
“…The survey was used to collect quantitative date from sample of students, and it was distributed to the students during the second year of academic of 2019/2020, throughout the spread of the COVID-19 pandemic. During the questionnaire development process, the literature and related studies in this field, such as studies conducted by [70] . The questions were consisted of two parts.…”
Section: Study Toolsmentioning
confidence: 99%